Outsourcing the global war on terrorism : private military companies and American intervention in Iraq and Afghanistan - Lovewine, George C.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
The US military strategy in Iraq and Afghanistan made use of private military and private security companies on an unprecedented scale. In this environment, actions and operations can greatly affect the efficacy of the US military - creating unintended diplomatic and tactical consequences.
Keywords: Science; Science; Science, general